2011
DOI: 10.1590/s0102-311x2011001500012
|View full text |Cite
|
Sign up to set email alerts
|

Birth cohort differences in anthropometric measures in the older elderly: the Bambuí cohort study of aging (1997 and 2008)

Abstract: The aim of this study was to evaluate the effect of birth cohort on nutritional status among older elderly (71-81 years old) from the Bambuí Cohort Study of Aging, conducted in Brazil in 1997 and 2008. We compared the two birth cohorts - 1916-1926 (older cohort) and 1927-1937 (recent cohort) - considering body mass index (BMI = weight/height²), waist circumference (WC) and prevalence of overweight (BMI ³ 27kg/m²). BMI (β = 0.09, 95%CI: 0.04, 0.15) and prevalence of overweight (PR = 1.02; 95%CI: 1.01; 1.03) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
3
3
1
3
Order By: Relevance
“…5 . Similar results for men, but different results for women, have been reported in another study 16 which evaluated birth cohort effects on the nutritional status of older adults aged 71 to 81 years, who participated in the 1997 and 2008 Bambuí (Minas Gerais, Brazil) cohort study of aging. The proportion of overweight, BMI and WC of older adults born in 1916-1926 (old cohort) was compared to those of older adults born in 1927-1937 (recent cohort).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…5 . Similar results for men, but different results for women, have been reported in another study 16 which evaluated birth cohort effects on the nutritional status of older adults aged 71 to 81 years, who participated in the 1997 and 2008 Bambuí (Minas Gerais, Brazil) cohort study of aging. The proportion of overweight, BMI and WC of older adults born in 1916-1926 (old cohort) was compared to those of older adults born in 1927-1937 (recent cohort).…”
Section: Resultssupporting
confidence: 81%
“…In the present study no differences between genders, as generally reported in other studies 16,18 , were observed. This finding is probably related to cultural differences between countries and/or regions of Brazil.…”
Section: Resultssupporting
confidence: 78%
“…Além disso, estudo prévio nessa população mostrou que o efeito da incapacidade, desfecho da presente análise, na mortalidade foi semelhante entre homens e mulheres, o que pode minimizar este impacto nos resultados apresentados 38 . Uma possível explicação é a constatação de aumento do sobrepeso entre os homens, enquanto a população feminina manteve a mesma prevalência de sobrepeso e reduziu os valores médios da circunferência da cintura, entre 1997 e 2008 39 . Sabe-se que existe um efeito do sobrepeso na determinação da incapacidade em populações idosas 19,25,36,40 , chamando atenção para o aumento do sobrepeso entre os homens, o que pode estar associado à ausência de efeito de período neste subgrupo e ao mesmo tempo ser menor nas coortes mais jovens, diferentemente do observado entre as mulheres.…”
Section: Figuraunclassified
“…A Brazilian study, found in the literature review, analyzed two birth cohorts (1916 -1926 and 1927 -1937), with elderly who participated in the Bambuí Project (Minas Gerais). This study found a higher prevalence of overweight (BMI ≥ 27 kg/m 2 ) in men in the birth cohort 1927 -1937 8 .…”
Section: Introductionmentioning
confidence: 47%